Implementasi Pembelajaran Al-Qur’an Hadis dalam Membentuk Akhlak Karimah Peserta Didik - Rosdiana, Rosdiana; Setiawan, Hasrian Rudi (TSAQOFAH, 2025)
The study is grounded in the pivotal role of Al-Qur’an Hadis instruction in shaping students’ akhlak karimah. The research objective is to determine the contribution of Al-Qur’an Hadis learning to the formation of akhlak karimah among Grade X students at MA Rohani Ikhwanul Muslimin. Employing a Classroom Action Research design, the study involved the Al-Qur’an Hadis subject teacher as a collaborator and proceeded through iterative cycles of planning, implementation, observation, and reflection. The findings indicate that Al-Qur’an Hadis learning makes a tangible contribution to instilling virtuous values—such as honesty, discipline, politeness, and respect for teachers. The study concludes that a contextual approach, role modeling, and habituation within Al-Qur’an Hadis instruction effectively cultivate students’ noble character. The contribution lies in evidencing a practical, cyclical model of faith-based pedagogy that systematically strengthens character formation in the Islamic secondary school context.